(untitled) (Applied Biological Research, 2023)
Induction of several types chlorophyll and viable morphological mutations were studied in M2 generation of non-basmati aromatic Badshabhog rice in all five different doses (200, 250, 300, 350 and 400 Gy) of gamma rays. Chlorophyll frequency was increased with increasing dose of gamma rays. Among different chlorophyll mutations albino was the most frequent type. Several morphological mutants such as short-stature, early maturity, increased tillering, dark green broad leaf, narrow leaf, short exerted panicle, complete spikelet sterility, double-triple spikelet, double kernel within spikelet and lodging resistant type were appeared with variable frequencies by different doses of gamma rays in 2,07,960 individual plantlets from M2 population. Among them short-stature mutant was predominate type. A nonlinear relationship was noticed between dose of gamma rays and frequency of viable mutations. The mutagenic efficiencies were increased with increase in irradiation dose but no relationship between the doses of mutagen and mutagenic effectiveness was established. Less damages in biological traits such as lethality, injury and sterility were observed at 200 to 300 Gy dose of gamma rays. Desirable mutants were found at 200 and 300 Gy.